Zbornik povzetkov / 20. dnevi varstvoslovja, Dolenjske Toplice - Marina Bajić; Modic, Maja; Areh, Igor; Flander, Benjamin; Lobnikar, Branko; Tominc, Bernarda (2019)
Book of Abstracts: 20th Days of Criminal Justice and Security. The changing political and security environment brings new challenges to the security of modern society, as reflected in the contributions of the 20th Conference of Security Studies, which bring professional and scientific reflection on ways and resources to ensure the security of modern society. Proceedings of the five round tables and summaries of contributions from fourteen thematic sections on counterfeit drugs, policing in rural areas, pluralisation of police activity, various forms of violence and its consequences for victims, crime, prevention and recognition of radicalization, fundamental rights in police procedures, protection against natural and other disasters, criminal and security-terminology, issues and challenges in the field of criminalistics and criminology, police management and ethics and integrity in the police, information security, social network security, detective activity, criminal enforcement sanctions and alternative penalties, modern technologies in security, personal data protection and other current security challenges of modern society.
Keywords: Days of security; security; security in local communities; police activity; criminology; criminalistics, information security; penology; radicalization; detective activity; rotection against natural and other disasters